2015
DOI: 10.1111/clr.12707
|View full text |Cite
|
Sign up to set email alerts
|

Topical applications of vitamin D on implant surface for bone‐to‐implant contact enhance: a pilot study in dogs part II

Abstract: With the limitation of animal studies, topical application of vitamin D on dental implants could reduce crestal bone loss and increase 10% more bone-to-implant contact at 12-week follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 46 publications
0
44
0
2
Order By: Relevance
“…117 Similar results were reported in mice with chronic kidney disease (CKD), suggesting that vitamin D treatment may be an effective approach for implant placement in patients with CKD. 124 Recently, the effect of topical application of vitamin D (10%) 125 and melatonin (5%) 126 solutions on the surface of immediate implants placed in dogs was evaluated. Both topical applications improved significantly new bone formation around implants and reduced crestal bone loss at 12 weeks following surgery, 126 standing out the positive correlation between vitamin D and early stages of osseointegration.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
“…117 Similar results were reported in mice with chronic kidney disease (CKD), suggesting that vitamin D treatment may be an effective approach for implant placement in patients with CKD. 124 Recently, the effect of topical application of vitamin D (10%) 125 and melatonin (5%) 126 solutions on the surface of immediate implants placed in dogs was evaluated. Both topical applications improved significantly new bone formation around implants and reduced crestal bone loss at 12 weeks following surgery, 126 standing out the positive correlation between vitamin D and early stages of osseointegration.…”
Section: Cholesterol and Fatty Acidsmentioning
confidence: 99%
“…Furthermore, in another study, after 8 weeks of oral vitamin D treatment, increased peri‐implant bone density, bone‐implant contact, and peri‐implant trabecular microstructure were demonstrated in ovariectomized rats . In an animal model, in which the effect of topical application of a solution of vitamin D (10%) on the surface of immediate implants was evaluated, it was shown that there was a positive correlation between vitamin D and the early stages of osseointegration, and vitamin D improved new bone formation . Similarly, in a case‐control study investigating the failure of immediate implant osseointegration, it was concluded that severe vitamin D deficiency had a negative effect on osseointegration .…”
Section: Discussionmentioning
confidence: 91%
“…6 In an animal model, in which the effect of topical application of a solution of vitamin D (10%) on the surface of immediate implants was evaluated, it was shown that there was a positive correlation between vitamin D and the early stages of osseointegration, and vitamin D improved new bone formation. 25 Similarly, in a case-control study investigating the failure of immediate implant osseointegration, it was concluded that severe vitamin D deficiency had a negative effect on osseointegration. 26 Waskiewicz et al reported the importance of vitamin D in different biological and metabolic processes and in the regulation of phosphocalcic metabolism and reported that vitamin D deficiency may be a risk factor that adversely affects bone healing and osseointegration in dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 studies were considered for the literature review, 9 were animal studies and 5 studies used human subjects. The literature review in animals demonstrated that administration of vitamin D can induce bone formation as well as strengthen and support the interaction between bone and implants 29 31 . Locally applied vitamin D may escalate the bone-implant contact percentage by 10% 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies have found that vitamin D is markedly beneficial to the cardiovascular 16 , immune and respiratory systems 17,18 . Even though the significance of vitamin D and its involvement in bone metabolism have been well documented [19][20][21][22][23][24][25][26][27][28][29][30][31] , limited studies have been conducted on the effects of osseointegration of implants in dental patients. Specifically, the majority of them have been performed in animal experimental models [20][21][22][23][24][27][28][29]31 and only a small number in humans [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%